FACTORS INFLUENCING POST BOKO-HARAM INSURGENCY VULNERABILITY OF CROP FARMERS IN NORTH-EAST, NIGERIA - Umar, U.; Tafida, A. A.; Ahmad, M. E.; Mohammed, U. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study assessed Factors Influencing Post Boko-Ha Insurgency Vulnerability of Crop Farmers in North-East, Nigeria. The study specifically described the socio-economic characteristics of Crop farmers, determined the factors influencing Post Boko-haram insurgency vulnerability of crop farmers, and identified the constraints hindering effective implementation of adaptation strategies among the respondents. The study employed a multi-stage sampling technique to select 387 household heads from insurgency-affected communities. Primary data were collected using structured questionnaires and analysed with descriptive and inferential statistics. The result revealed that gender profile of households indicates that 68.5% were male-headed while 31.5% were female-headed, and the age structure of household heads revealed that 82.4% were between 40 and 59 years. Educational attainment of household heads shows considerable variation. While 33.3% had secondary education and 19.6% had tertiary education, 8.3% had no formal education and 16.0% only informal education. Cooperative membership was reported by 33.9% of respondents, while 66.1% did not belong to any cooperative society. Logistic regression results showed that education level (β = 0.372, p < 0.01), access to credit (β = 0.418, p < 0.05), cooperative membership (β = 0.285, p < 0.05), and extension access (β = 0.354, p < 0.01) significantly influenced crop farmers vulnerability. Household size (β = 0.193, p < 0.1) and farm size (β = 0.226, p < 0.05) positively influenced vulnerability. Lack of farm tools was reported as severe by 81.9% and very severe by 6.5% of respondents, yielding a mean score of 1.95. Lack of machinery, however, ranked among the most severe problems, with 64.1% rating it very severe and a mean of 2.62. Fertilizer shortages were reported as very severe by 53.7% of households, while 70.8% were identified having inadequate access to improved seeds were some of the constraints identified. The study concludes that crop farmers’ vulnerability is shaped more by access to education, cooperatives, seeds, extension, climate information, and farmland than by demographic characteristics. It is recommended that government and supporting agencies should strengthen access to agricultural inputs and technologies, enhance land tenure security and rural infrastructure, expand financial inclusion and market support, and improve extension services and climate information delivery.